Hubungan dukungan keluarga dengan kualitas hidup lansia - Dasrina Dasrina; Desi Yulastri; Eka Sutrisna; Ita Safriana (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Increasing life expectancy has led to a continued rise in the number of elderly people, making attention to their well-being and quality of life increasingly important. One factor that plays a role in determining the quality of life for older adults is family support. Purpose: To determine the relationship between family support and the quality of life of the elderly. Method: This study used a quantitative design with a cross-sectional approach. The study population was all 40 elderly people in Panglima Sahman Village, using a total sampling technique to sample the entire population. Data were collected using a questionnaire and analyzed univariately and bivariately using the Chi-Square test with SPSS. Results: The majority of elderly people (29 respondents) received family support. The quality of life of elderly people was in the adequate and good categories, respectively, with 15 respondents (37.5%). Furthermore, among elderly people who did not receive family support, the majority had a poor quality of life (45.5%). The statistical test results showed a p-value of 0.000 (<0.05), indicating a significant relationship between family support and elderly people's quality of life. Conclusion: There is a significant relationship between family support and quality of life in older adults. Family support plays a crucial role in improving the physical, psychological, and social well-being of older adults, making family involvement a key factor in efforts to improve quality of life for older adults.   Keywords: Attitude;  K3RS Training; Knowledge; SMK3RS.   Pendahuluan: Peningkatan usia harapan hidup menyebabkan jumlah lansia terus meningkat, sehingga perhatian terhadap kesejahteraan dan kualitas hidup lansia menjadi semakin penting. Salah satu faktor yang berperan dalam menentukan kualitas hidup lansia adalah dukungan keluarga. Tujuan: Untuk mengetahui hubungan dukungan keluarga dengan kualitas hidup lansia. Metode: Penelitian ini menggunakan desain kuantitatif dengan pendekatan cross sectional. Populasi penelitian adalah seluruh lansia di Desa Panglima Sahman sebanyak 40 orang dengan teknik total sampling sehingga seluruh populasi dijadikan sampel. Data dikumpulkan menggunakan kuesioner dan dianalisis secara univariat serta bivariat menggunakan uji Chi-Square dengan bantuan SPSS. Hasil: Sebagian besar lansia mendapatkan dukungan keluarga sebanyak 29 responden (72.5%). Kualitas hidup lansia berada pada kategori cukup dan baik masing-masing sebanyak 15 responden (37.5%). Kemudian pada lansia yang tidak mendapatkan dukungan keluarga, sebagian besar memiliki kualitas hidup kurang baik (45.5%). Hasil uji statistik menunjukkan nilai p value = 0.000 (< 0.05) yang berarti terdapat hubungan signifikan antara dukungan keluarga dengan kualitas hidup lansia. Simpulan: Terdapat hubungan yang signifikan antara dukungan keluarga dan kualitas hidup lansia. Dukungan keluarga berperan penting dalam meningkatkan kesejahteraan fisik, psikologis, dan sosial lansia, sehingga keterlibatan keluarga menjadi faktor kunci dalam upaya peningkatan kualitas hidup lansia.   Kata Kunci: Pelatihan K3RS; Pengetahuan; Sikap; SMK3RS.